1996
DOI: 10.1046/j.1365-3156.1996.d01-89.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum malaria in the first year of life in an area of intense and perennial transmission

Abstract: SummaryA longitudinal study of Plasmodium falciparum malaria in infants in Idete village, south-eastern Tanzania, was conducted over a period of 14 months in order to determine the incidence of P. falciparum infection and clinical malaria in the first year of life. Of 1356 blood slides from cross-sectional surveys, 52.1% were positive for asexual stages of P. falciparum. There were marked increases in P. falciparum prevalence, parasite densities, overall fever incidence and the incidence of malaria fevers with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
113
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 32 publications
6
113
2
Order By: Relevance
“…1993SMITH et al,. , 1998aKITUA et al, 1996) and parasites usually cannot be detected by PCR in blood films found to be aparasitaemic by microscopy (FELGER et al, 1999b). As children grow older, parasite densities fall and the prevalence of microscopically sub-patent parasitaemia increases (FELGER et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1993SMITH et al,. , 1998aKITUA et al, 1996) and parasites usually cannot be detected by PCR in blood films found to be aparasitaemic by microscopy (FELGER et al, 1999b). As children grow older, parasite densities fall and the prevalence of microscopically sub-patent parasitaemia increases (FELGER et al.…”
Section: Discussionmentioning
confidence: 99%
“…Children under one year old form the age group most susceptible to clinical malaria in Kilombero (KITUA et al, 1996). In these children with the highest recovery rates, acute episodes of clinical malaria are positively associated with multiplicity of infection ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to detect any differences in parasite densities or PCV levels of children with different genotypes or haemoglobin types, analysis of covariance, again with a random effect term were performed. Effects of age on parasite prevalence, density and PCV levels were reported previously (Kitua et al 1996), and age was included as a covariate in all present analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Within a longitudinal study, consisting of epidemiological and parasitological surveys of malaria morbidity in the first year of life, 204 infants were randomly selected and followed for one year (Kitua et al 1996). Blood samples of the children were collected during household visits in eight cross-sectional surveys as previously reported (Kitua et al 1996).…”
Section: Study Population and Samplingmentioning
confidence: 99%
See 1 more Smart Citation